2020
DOI: 10.1080/19336950.2020.1730020
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 inhibits smooth muscle cell phenotype switching in a mouse model of abdominal aortic aneurysm

Abstract: The natural outcome of abdominal aortic aneurysm (AAA) is that of slow progression and ultimate rupture, then a life-threatening hemorrhage consequently. Ruptured AAA is a dramatic catastrophe and constitutes one of the leading causes of acute death in elderly men. However, the mechanism of AAA is still unclear. Transient receptor potential vanilloid (TRPV) family has protective effects in cardiovascular diseases. In this study, we revealed the expression and the pathogenesis of TRPV1 in a mouse AAA model. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The transient receptor potential vanilloid (TRPV) family is expressed abundantly in cerebral artery VSMCs and has been shown to be an important mediator of vascular tone ( Guibert et al, 2011 ). The overexpression of TRPV1 has been found to inhibit Ang II induced VSMC migration and phenotype transitions from a contractile to secretory state ( Wang and Jia, 2020 ). Another study found that activated TRPV1 inhibited VSMC proliferation, migration, and ROS production by upregulating the expression of PPARα ( Zhou et al, 2021 ).…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…The transient receptor potential vanilloid (TRPV) family is expressed abundantly in cerebral artery VSMCs and has been shown to be an important mediator of vascular tone ( Guibert et al, 2011 ). The overexpression of TRPV1 has been found to inhibit Ang II induced VSMC migration and phenotype transitions from a contractile to secretory state ( Wang and Jia, 2020 ). Another study found that activated TRPV1 inhibited VSMC proliferation, migration, and ROS production by upregulating the expression of PPARα ( Zhou et al, 2021 ).…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…AA is characterized by permanent dilation of the arteries to 1.5 times their normal size, making them prone to rupture or dissection ( Malecki et al, 2020 ). AA is a chronic degenerative disease involving the breakdown and loss of the structural extracellular matrix (ECM) of the aortic wall, leading to progressive thinning, weakness and eventual rupture of the vessel wall ( Wang and Jia, 2020 ; Dahal et al, 2022 ). Chronic inflammatory infiltration, degradation of collagen and elastin, and other pathological changes are also involved ( Wang and Jia, 2020 ; Dahal et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…AA is a chronic degenerative disease involving the breakdown and loss of the structural extracellular matrix (ECM) of the aortic wall, leading to progressive thinning, weakness and eventual rupture of the vessel wall ( Wang and Jia, 2020 ; Dahal et al, 2022 ). Chronic inflammatory infiltration, degradation of collagen and elastin, and other pathological changes are also involved ( Wang and Jia, 2020 ; Dahal et al, 2022 ). AA is a life-threatening condition, with approximately 150,000–200,000 deaths reported worldwide annually, leading to a significant socioeconomic burden and causing great suffering to the families of patients ( Golledge, 2019 ; Wen et al, 2020 ; Ibrahim et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is one of the leading causes of cardiovascular death, as clinical 3 treatments are limited [1][2][3]. Vascular smooth muscle cells (VSMCs) are the main components of the vascular wall and play an important role in maintaining the vascular structure.…”
Section: Introductionmentioning
confidence: 99%